Residential Segregation by Race in U.S. Metropolitan Areas An Analysis Across Cities and Over Time - Schnare, Ann B.; Urban Inst., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
There is a need to understand more clearly the forces that work to generate and maintain a segregated housing market. There is also a need to formulate statistical measures of segregation, so that developments in future years can be assessed against the past. This report was designed with these two objectives in mind. The analysis is primarily concerned with the experience of the 1960's, when the socioeconomic status of minorities was undergoing significant improvement, new civil rights initiative had emerged from the courts, and surveys revealed an apparent weakening in the prejudices of blacks and whites alike. Since the 1960's seemed particularly ripe for an increase in integration, developments within those years provide some telling clues to the prospects for future change. A brief review of recent trends in attitudes, incomes, and policies which might have encouraged the breakdown of segregated living patterns is first provided. Statistics which describe the segregation of urban households in 1960 and 1970 actually show an overall increase in the level of segregation during the ten year period. Social, economic, and market factors that might affect the location of blacks and whites within a housing market are considered. The findings suggest that racial segregation may continue to plague the majority of urban areas. (Author/AM)
Sponsoring Agency: Department of Housing and Urban Development, Washington, DC. Office of Policy Development and Research.
Contract Number: H-2162R.
ERIC Note: Not available in hard copy due to print quality of original document.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Change Agents; Housing Discrimination; Housing Opportunities; Minority Groups; Racial Differences; Racial Factors; Racial Segregation; Residential Patterns; Trend Analysis; Urban Areas; Reports, Research